Дослідження міцності роз'ємного різьбового з'єднання з великим кроком в деталях з армованих композиційних матеріалів - Некрасов, Сергій Сергійович; Довгополов, Андрій Юрійович (НТУ "ХПІ", 2018)
З метою дослідження міцності, запропонованого роз’ємного з’єднання для деталей з армованих композиційних матеріалів (АКМ), були проведені дослідження зі зміною основних параметрів що найбільше впливають на працездатність з’єднання. Для запропонованого з’єднання, круглої різьби з великим кроком, змінювалися такі основі параметри я крок різьби р та глибина профілю різьби t. Отримані значення сили, дозволили встановити, що запропоноване роз’ємне з’єднання за характеристиками міцності, при всіх встановлених параметрах наближається, за показниками міцності, до з’єднання з аналогічними параметрами виконаному в металі. За рахунок виконання повного факторного експерименту за класичною схемою його виконання, були встановлені основні параметри при яких показники міцності будуть найкращими, для нашого випадку значення кроку різьби складатиме р = 4 мм, а значення глибини профілю різьби t = 0.9 мм.

With the purpose of research of durability, offered sectional connection for details from the reinforced composition materials (RCМ), there were undertaken studies with the change of basic parameters that most influence on the capacity of connection. For the offered connection, round screw-thread with a stride, such parameters as step of screw-thread of р and depth of profile of screw-thread of t changed. These basic parameters varied within the following limits step of screw-thread p in the range from 1 to 4 mm, and depth of profile of screw-thread t is from 0.5 to 1 mm. Mechanical processing of this connection was carried out on the newly developed technology, the detailed processing technology described in [1]. For processing, a CNC milling machine was used. Experimental strength tests were carried out using special equipment, a universal rupture machine P20. The threaded connection was made in a plate of 190x107x16 mm, the material from which the specified plate was made of fiberglass (0.5 to 0.5 mm gratings) 0.2 mm thick and EPOXY-520 epoxy resin. Got values of force, allowed to set that sectional connection on descriptions of durability, at all set parameters approached, on the indexes of durability, to connection, with analogical parameters executed in a metal. Due to implementation of complete factor experiment on the classic chart of his implementation, basic parameters were set at that indexes of durability will be the best, for our case a step of screw-thread will be р = 4 mm, and value of depth of profile of screw-thread of t = 0.9 mm.
Keywords: АКМ; напруження; кругла різьба; працездатність; крок різьби; глибина профілю різьби; voltages; round screw-thread